The Effect of Semantic Mapping Strategy On Students’ Speaking Achievement In Smp Budi Murni 3 - Firdha Sabrina Fitri Sinurat (JADEs Journal of Academia in English Education, 2020)
This study aims to discover the effect of applying Semantic Mapping Strategy on students’ speaking achievement. It will be conducted by using experimental research design. The population of this research is the eight (VIII) grade students of SMP Budi Murni 3. The samples of the research are two classes divided into two groups, experimental and control group which will be chosen by using random sampling technique. Thirty-one students will be taken as the samples. The experimental group will be taught by using Semantic Mapping Strategy, while the control group will be taught by without using Semantic Mapping Strategy. After analyzing the data, it was found that the value of tobserved was 3,12 with the degree of freedom (df)=60 at the level of significance p (0,05) = 2,000. It means that tobserved is higher than ttable (3,12>2,000). The result of this study shows that Semantic Mapping Strategy is significant effect on students’ speaking achievement.